Incidence of Typhoid Fever in Nineveh Province from 2018-2022 - Ali Adel Dawood (Cam & Sakura Medical Journal)
Objective: Typhoid fever is a grave and highly contagious illness caused by Salmonella typhi that is primarily spread through mucosal exposure to bacteria typically found in the gastrointestinal tract. his study focused on identifying the causes of the epidemic, predicting which populations are more susceptible to the disease, and evaluating the effectiveness of health measures set in place to prevent its spread in the Nineveh province. Material and Methods: The study focused on patient data collected between 2018 and 2022. The count of infected individuals belonging to the sick group was authenticated based on the clinical diagnosis and laboratory investigation. Ultimately, we used a statistical analysis tool with SPSS version 25. Results: The highest number of cases was registered on the left side of Mosul, followed by cases spreading to Shekhan, Hamdaniya, and Baaj, in that order. The main proportion of the cases was among 15-45 years and older than of 45 years old people with a relatively high correlation coefficient of (p<0.01). Conclusion: The major reason for the spread of typhoid is the combination of poor quality of life and improper activities of the health system, which eventually lead to serious public health conditions. Strengthening the health-care system and raising public awareness about the disease are the two most crucial steps to slow down the outbreak.